Dominican Republic : Social and Structural Policy Review, Volume 2 - World Bank (Washington, DC, 2013)
The report outlines the macroeconomic stability in the Dominican Republic during the 1990s, suggesting its strong economic growth, and poverty reduction, will contribute to the gradual transformation the country is undergoing towards policy reform. It analyzes poverty, especially severe in rural areas, where misdirected agriculture policies, and insufficient public investments, such as education, limit opportunities. But, the advancing trade liberalization, is expected to reduce export taxes, and although displaced industrial, and agricultural activities will be subjected to adjustment costs, there will nonetheless be improvements in consumers' welfare, and real wages. However, public resources for education remain very low, particularly for secondary education, and this should be considered as key element of the government's poverty reduction strategy, in addition to the establishment of safety nets to curtail malnutrition, and expand health, and sanitation programs, to tackle the extreme poverty. Recommendations suggest, first, to reduce macroeconomic vulnerabilities, through tight fiscal, and monetary policies, and, second, implement reforms, to prod a business environment, and, a strengthened banking sector, through market, and regulatory mechanisms.